Climatology for Agroforestry Systems - Rawat, Laxmi (Indian Forester, 1997)
In agriculture and forestry, climatic information has as much importance as in other fields. From the time the seeds are sown until plants are harvested and stored, crops more or less depend on weather, particularly during certain critical periods in their growth. The appropriate practice ofagroforestry depends upon combination of climate and other factors. The systematic intercropping of trees and shrllbs with agricultural crops changes microclimatic conditions, which have reciprocal consequences on productivity. Shelterbelts and mulches modify a number of meteorological variables, thereby increasing yield of the crop. A number of studies highlighting these influences of shelterbelts and mulches on microclimate and yield are reported in this article.